The Relationship Between Medication Adherence and Nutritional Status with Random Blood Glucose Levels Among Patients with Type 2 Diabetes Mellitus at Plaju Community Health Center - Noviyanti Noviyanti; Yesi Astri; Indriyani Indriyani; Rury Tiara Oktariza; Ratih Pratiwi; Marina Dwi Putri (Universitas Muhammadiyah Palembang, 2026)
ABSTRACTType 2 diabetes mellitus is a group of chronic metabolic diseases characterized by hyperglycemia, which requires ongoing medical care and reduction of risk factors. Compliance with treatment in diabetic patients is a major factor in controlling blood sugar levels, so that it can affect treatment outcomes. Nutritional status is one of the problems that play a role in Diabetes Mellitus because type 2 diabetes mellitus patients with more nutritional status tend to have higher blood sugar levels than patients with normal nutritional status. This type of research is an analytic observational study using a cross-sectional design. The number of samples in this study were 120 samples. The sampling method in this study used a consecutive sampling technique. Based on the results on the variables of medication adherence with blood sugar levels, the results of bivariate analysis showed that there was a significant relationship between medication adherence and blood sugar levels in type 2 diabetes mellitus patients at the Plaju Health Center. While the results on the variable nutritional status and blood sugar levels show that there is a significant relationship between nutritional status and blood sugar levels in type 2 diabetes mellitus patients at the Plaju Health Center. Keywords : Medication Adherence, Nutritional Status, Blood Sugar Levels, Type 2 Diabetes Mellitus